Advances in various pretreatment strategies of lignocellulosic substrates for the production of bioethanol: a comprehensive review - Wondmagegn Wonago Kululo; Nigus Gabbiye Habtu; Metadel Kassahun Abera; Zenamarkos Bantie Sendekie; Solomon Workneh Fanta; Temesgen Atnafu Yemata (Discover Applied Sciences)
Abstract Lignocellulose biomass (LCB) is abundantly available in the world. Effective utilization of LCB requires an efficient pretreatment process that maximizes percentage-reducing sugar recovery. However, developing advanced pretreatment techniques that will help in full-scale biomass valorization is the bottleneck of the biofuel industry. This review paper covers the recent achievements of research in the various pretreatment technologies employed in lignocellulosic substrates conversion into bioethanol. The LCB primarily constitutes cellulose, hemicellulose, and lignin. The lignin is recalcitrant to enzymatic and microbial action. A huge amount of energy and resources is spent on reducing and removing the lignin part of the biomass. Effective pretreatment must disrupt the structure and aid in biomass dissociation. Pretreatment approaches are usually classified as physical, chemical, physicochemical, and biological. The various pretreatment approaches are substrate-specific and the choice of the pretreatment methods depends on the composition of the specific biomass. However, a single pretreatment technique has drawbacks in cost-effectiveness, environmental safety, and energy utilization. Recently, combined pretreatment has gained huge popularity because it minimizes the above-mentioned drawbacks. The review focused on the environmental impact of biorefineries within the context of a green economy. It also highlights the effect of combined pretreatment strategies on energy efficiency and environmental preservation. Therefore, this review paper summarizes various pretreatment techniques and recent advances in combined pretreatment approaches.